A Critical Analysis of External Factors Affecting World Rankings of Iranian Universities - Atefeh Rigi; nematollah azizi; Abolvahab purghaz (پژوهش در نظام‌های آموزشی, 2020)
As a qualitative research, this study aims to investigate external challenges of Iran's higher education system based on the global rankings’ indicators in which Ruth Wodak’s method of critical discourse analysis was applied. Participants included 16 scholars and senior officials from Higher Education Institutions in Tehran whose were selected via snowball sampling method. Semi-structured interviews were applied to collect data based on theoretical saturation which were lasting between 30 and 60 minutes. For data validation both participants review (member check) and review by external experts (external check) were applied. critical discourse analysis were used to analyze data. The finding revealed that policy-making challenges including “diversity and lack of coordination in policies of institutions determining higher education policies, lack of attention to determining missions in policy-making, not specialized policy-making processes and not using research results in them”, economic challenges including “lack of attention to income generation of universities in economic policies of Iran, lack of attention to knowledge-based economy for Iran’s economic development”, and sociocultural challenges including “low importance of science in the Iranian society, lack of attention to education of global citizens, and special attention to the local ‘We’”, are main external factors which have affected Iranian higher education system leading to low global ranking of Iranian universities. In this regard, some strategies are presented to improve the global ranking of Iranian universities.